Dutch, the world tallest, are shrinking in height: lessons from the cases of Japan and South Korea - Mori, Hiroshi (European Journal of Applied Sciences, 2021)
Dutch (men aged 20-21) grew in height fast and steadily from 173.5 cm in the mid-1950 to 182.3 cm in the 1980s, and 184 .0 cm in the late-1990s, “the world tallest” and levelled off, or mean height even declined by 0.3-0.5 cm, or even more in in the latest decade, despite growing social-economic environments. In North-East Asia, men in South Korea grew fast and steadily in height to overtake their Japanese peers by 3.0 cm in the mid-2000s and then stopped growing taller despite continued economic prosperity and increased per capita consumption of animal protein in their diets. The author derived per capita consumption of major food products from household expenditure surveys, classified by age groups of household head. He discovered that children in growing ages, 0~9, 10~19, started to turn away from vegetables in the early-1990s, to consume only 25% of the vegetables eaten by adults in their 50s in the mid-2000s and 10% of vegetables by the older cohorts in their 50s in the end of the 2010s. Some four decades ago, children in Japan started to turn away from fruit. They ceased to grow taller at all ages in the 1990s, despite continued higher consumption of animal protein. The Netherlands has been appreciably lower in per capita consumption of vegetables, compared to other North-European countries. Further empirical investigations along cohorts are needed, in order to determine if they have reached maximum genetic potentials.